Effect of Penicillium chrysogenum Concentration on The Production and Characteristic of Pectinase Enzyme from Pineapple (Ananas comosus) Peel Waste - Bayu Setyaji; Maria Marina Herawati (The University of Lampung, 2022)
This study aimed to determine the effect of various concentrations of Penicillium chrysogenum isolates on the production of pectinase enzymes from pineapple peel waste. The experiment was arranged in CRD (completely randomized design) with six different isolate concentrations (4%; 8%; 14%; 16%; 20%; and 24%). The experiment constituted of three stages, namely production of enzymes by using Penicillium chrysogenum isolates, enzyme harvesting with a goal to obtain a crude extract of the enzymes, and enzyme characterization. Parameters in this study included enzyme activity, optimum temperature, optimum pH, Km value, and Vmax value. Results showed that the highest yield (1.87 g) was obtained from the 24% treatment and the lowest in the 4% treatment at 1.63 g. The highest enzyme activity in the 24% treatment was 1.924 U/ml and the lowest was in the 4% treatment, namely 0.949 U/ml. The highest Vmax value was 0.690 U/ml from the 24% treatment and the lowest was 474 from the 4% treatment. Conversely, the highest Km (0.040 mg/ml) value was found in 4% treatment and the lowest (0.016 mg/ml) was observed in 24% treatment. Keywords: Characteristics, Enzyme, Fungi, Pectinase, Pineapple